An echocardiographic study of the interventricular septum in constrictive pericarditis. Issue 7 (July 1976) - Gibson, T C; Grossman, W; McLaurin, L P; Moos, S; Craige, E
Abstract : Ten patients with constrictive pericarditis were studied echocardiographically with specific reference to inter-ventricular septal dynamics. Abnormal movement of the interventricular septum was present in 8 patients and consisted of flattening in systole and unusual posterior motion in diastole. The aetiology of this type of movement is at present unknown but may be related to restriction of normal cardiac rotational dynamics. The interventricular septum also showed diminished degree of thickening (mean 21-2%). The amplitude of excursion was generally at the upper limit of or greater than normal. Left ventricular posterior wall amplitude of excursion was normal. Flattening of left ventricular posterior wall diastolic movement was seen in 4 patients. Right ventricular end-diastolic dimension was slightly increased (1-2 to 1-7 cm/m2) in 5 of 8 patients with abnormal septal motion, but no haemodynamic evidence of diastolic volume overload was found. Posterior pericardial thickening was noted echocardiographically when posterior calcification was present. We conclude that the most common though non-specific feature of the echocardiogram in patients with constrictive pericarditis is abnormal septal motion. Flattening of left ventricular posterior wall diastolic movement, posterior pericardial thickening, and epicardial-pericardial separation may also occur.